Pengaruh pemberian pangan antioksidan terhadap kadar malondialdehid plasma mahasiswi penyuka gorengan - Inti Makaryani; Leily Amalia; Novi Rizqi Ramadhani; Karina Indah Pertiwi; Desy Dwi Aprillia (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2014)
Background: Antioxidant elements such as vitamin C, vitamin E, lycopene, chlorophyl, polyphenol, and other flavonoid existed on various foods of fruits, vegetable, tea, coffee, and others. The foods are usually consumed in our every single day. Some previous studies had shown that there were various benefits of antioxidant elements for animal and human health. However, the antioxidative effect of the antioxidant elements in combating free radicals in the body is not similar to each other.Objective: This study was aimed to analyze the effect of antioxidant foods (green grass jelly drinks, tomato juice, papaya, and black tea) on blood levels of malondialdehyde (MDA) among college students.Method: The study was designed by pre-post test control study. Subjects were divided into five groups, consisted of four intervention groups and one control group. Every group consisted 6 persons. Each subject was asked to consume one kind of antioxidant foods in a single serving size per day for 21 days.Results: All of the subjects who consumed fried foods had high MDA levels in pre-intervention. The results of this study showed that MDA level in the group of green grass jelly drink decreased significantly (p<0.05). Plasma MDA levels tend to decline between pre and post intervention in the group of tomato juice, papaya, and tea, but they were not statistically significant (p>0,05).Conclusion: The antioxidant foods which can reduce plasma MDA level were green grass jelly drink. However, tomato juice, papaya, and tea can also reduce plasma MDA level, but not statistically significant.